2008
DOI: 10.1007/s12011-008-8129-4
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fluoride Ions upon Selected Enzymes of Protein Metabolism in Blood Plasma of Rabbits with Hypercholesterolemia

Abstract: Three-month studies were performed on 18 adult rabbits of New Zealand breed divided into three groups, with six animals in each: a control group on standard diet, a cholesterol group receiving 500 mg of cholesterol/100 g of feed per rabbit per 24 h (CH group), and a cholesterol + fluorine group (CH + F group) receiving 500 mg of cholesterol/100 g of feed per rabbit per 24 h and 3 mg of F(-)/kg of body weight per 24 h. The conducted studies proved that cholesterol in the applied dosage (500 mg cholesterol per r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…In addition, the toxic effect of thioacetamide has also been reported in many studies that when applied on different experimental animals, it may lead to an increase in serum creatinine levels [26][27][28]. This increase may occur due to a disturbance in Na + -K + pump of nephron and detachment of epithelial cells from renal tubules which causes nephropathy while damaging and destroying renal parenchyma [29]. Also, a study by Serag [12] reported an increase inurea and creatinine levels in mice after getting treated with TAA.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, the toxic effect of thioacetamide has also been reported in many studies that when applied on different experimental animals, it may lead to an increase in serum creatinine levels [26][27][28]. This increase may occur due to a disturbance in Na + -K + pump of nephron and detachment of epithelial cells from renal tubules which causes nephropathy while damaging and destroying renal parenchyma [29]. Also, a study by Serag [12] reported an increase inurea and creatinine levels in mice after getting treated with TAA.…”
Section: Resultsmentioning
confidence: 97%